The Effect of Acupuncture Therapy at ST 40 (Fenglong), SP 6 (Sanyinjiao) and Avocado Juice on Reducing Total Cholesterol Levels in High Cholesterol Cases in Duwetan Ngunut Jumantono - Imrok Atus Sholihah; Wahyu Eka Hastuti (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2024)
Introduction: Hypercholesterolemia is a condition where the cholesterol levels in the blood exceed normal levels. One of the non-pharmacological therapeutic treatments for patients with hypercholesterolemia is acupuncture therapy and providing nutritious food intake. This study aims to determine the effect of acupuncture points at ST 40 (Fenglong), SP 6 (Sanyinjiao) and avocado juice on reducing total cholesterol levels in cases of high cholesterol in Duwetan Ngunut JumantonoMethods: Design of this researchQuasy experimental with the two groups pretest-posttest design method. January - August 2023 in Duwetan Ngunut village, Jumantono, Karang Anyar. The sampling technique was Purposive Random Sampling of 38 research subjects. Data collection uses primary data, namely the results of measuring total cholesterol levels. Research analysis consisted of univariate analysis, bivariate analysis with Wilcoxon and Mann-Whitney tests.Results:There was an effect of acupuncture therapy at points ST 40 (Fenglong), SP 6 (Sanyinjiao) (p=0.0018) and a combination of avocado juice (p=0.0001) on reducing total cholesterol levels. There was a difference in the reduction in total cholesterol levels after being given the intervention (p=0.007) in the acupuncture therapy group (Mean= 219.79; SD= 39.35) and the avocado juice combination acupuncture group (Mean= 181.63 SD= 36.63).Conclusion:There was a decrease in total cholesterol levels after being given acupuncture therapy at points ST 40 (Fenglong), SP 6 (Sanyinjiao) and a combination of avocado juice in the Duwetan Ngunut Jumantono village community.